Knowledge, perceptions and uses of Crocodylus moreletii in Pantanos of Centla Biosphere Reserve - Ocampo-González, Paola; Rodas-Trejo, Jenner; González-Ramón, Mariana del Carmen (Ecosistemas y Recursos Agropecuarios, 2021)
The Pantanos of Centla Biosphere Reserve (PCBR) represent one of the main refuge, reproduction and feeding sites for the Morelet’s Crocodile (Crocodylus moreletii) in Mexico. The objective of the work is to identify the knowledge, perception, interactions,uses and benefits that inhabitants of the RBPC have towards the species. Between August and October 2018, semi-structured interviews with adults and environmental education workshops with children were carried out in four locations of the Reserve. Through the interviews, a remarkable knowledge about the Morelet’s Crocodile was identified, since people constantly interact with the species during activities such as fishing, showing interest andrespect towards it. The use and exploitation of the specie occurs in all localities and is mainly as food and medicine. The main factor that concerns the inhabitants in the conservation of the species is the contamination of rivers and lagoons with substances derived from the oil industry and agricultural activities. The activities with children demonstrated their ignorance regarding the ecological benefits of the Morelet’s Crocodile, as well as demonstrating that they are in favor of hunting various wild species. It is necessary to reinforce actions for the conservation of wildlife both in children and adults, since its consumption is a common activity within the Reserve, in addition to carrying out more studies that identify the presence of polluting substances in both animals and water and promote the dissemination of the results.